Competing Logics in Healthcare: Professional, State and Managerial - ScottRichard W. (Journal of Economic Sociology, 2010)
The authors of this paper were not only trying to through the light on the changes that have taken place in healthcare during the last 50 years in one of the American cities but also made an attempt to work out an analytical scheme applicable to study other fundamental institutional changes. Despite the fact that the used data period ends by 1995 the main tendencies are relevant nowadays as well.